Beginning teachers who teach Mathematics and the determining aspects of their professional development - Costa, Andressa Florcena Gama da; Morelatti, Maria Raquel Miotto [UNESP] (Univ Nove Julho, 2024)
This article presents the results of a qualitative research, developed over five years, whose objective was to investigate the role played by the degree course and school institution in the way Pedagogy teachers face early career dilemmas, especially for teaching Mathematics, which enable or limit professional development. Five teachers formed in public and private institutions participated in the research, who responded to a questionnaire and participated in episodic interviews. The data show gradual changes in the teaching of mathematics motivated by the initial training course. Moreover, the context in which they work influences and may even limit their autonomy in organizing their classes. The conclusion is that the course and the place of performance interfere in the following regulatory aspects of professional development: affinity/aversion to Mathematics; isolation/collaboration; conservatism/change and performance by trial and error versus reflective practice.
Keywords: teacher education; initiation to teaching; professional development; mathematics education